Fates of CD8+ T cells in Tumor Microenvironment - Maimela, Nomathamsanqa Resegofetse; Liu, Shasha; Zhang, Yi (Computational and structural biotechnology journal, 2019)
Studies have reported a positive correlation between elevated CD8+ T cells in the tumor microenvironment (TME) and good prognosis in cancer. However, the mechanisms linking T cell tumor-infiltration and tumor rejection are yet to be fully understood. The cells and factors of the TME facilitate tumor development in various ways. CD8+ T cell function is influenced by a number of factors, including CD8+ T cell trafficking and localization into tumor sites; as well as CD8+ T cell growth and differentiation. This review highlights recent literature as well as currently evolving concepts regarding the fates of CD8+ T cells in the TME from three different aspects CD8+ T cell trafficking, differentiation and function. A thorough understanding of factors contributing to the fates of CD8+ T cells will allow researchers to develop new strategies and improve on already existing strategies to facilitate CD8+ T cell mediated anti-tumor function, impede T cell dysfunction and modulate the TME into a less immunosuppressive TME.